HALAL ATAU HARAM CRYPTOCURRENCY SEBAGAI ALAT TRANSAKSI PEMBAYARAN?: MENDIALOGKAN DARI SUDUT PANDANG SYARIAH DAN REGULASI - Muhammad Fauzi; Mursal Mursal (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
People's lives and activities have become more Go-Digital. The proof can be seen from the means of payment transactions using digital currency (Cryptocurrency). Cryptocurrency is a decentralized system using peer-topeer technology (Blockchain) without being regulated and issued by a third party (such as a government/bank financial institution). It is different from fiat currency in physical form (paper money and coins) and non-physical fiat currency (giral money) which is centralized/regulated and issued by a third party. Therefore, this research aims to find out whether Cryptocurrency is halal or haram as a means of payment transactions by having a dialogue from a sharia point of view. This research also finds out whether Cryptocurrency is legal or illegal as a means of payment transactions by having a dialogue from a regulatory point of view in Indonesia. This research takes place using the Literature Review approach. This study shows that halal or haram Cryptocurrency as a means of payment transactions a dialogue from a sharia point of view, there are still differences of opinion, especially the parties giving fatwas (ulama, majlis, and sharia academics). Some parties decided Cryptocurrency was Halal (permissible/Mubah);, and some parties decided Cryptocurrency to Abstain; and some parties decided Cryptocurrency a total ban (Haram) (including MUI in Indonesia decided that Cryptocurrency as a means of payment was forbidden);. Meanwhile, a dialogue from a regulatory point of view in Indonesia, Cryptocurrency cannot yet become a means of payment transactions because they are contrary to existing laws and regulations and Bank Indonesia regulations. At the same time, Bank Indonesia has firmly stated that Cryptocurrency is an illegal means of payment transactions. In Indonesia, legal cryptocurrencies are only regulated in the regulations issued by PERMENDAG/BAPPETI, but only limited to commodities (assets).